Creative pedagogy: a case for teachers' creative learning being at the centre. Issue 3 (3rd July 2017) - Selkrig, Mark; Keamy, (Ron) Kim
Abstract: While educators in many parts of the world grapple with what creativity means in practice, discussions about creative pedagogy usually include the elements of creative teaching, teaching for creativity and creative learning. This article stems from a research project that occurred at a Preparatory to Year 9 school in Australia where we worked with staff to explore their understandings of creativity and creative learning in the Arts. We found that while students' creative learning is a fundamental element in a creative pedagogy framework, the notion of creative learning of teachers is largely overlooked in discourses of teachers' professional learning. Given the important role teachers play in student learning, we argue that teachers need to be informed not only about how to teach creatively and for creativity, but also how to consider possibilities and understand things in new ways, thereby making a case that a teacher's own creative learning is crucial.